Nucleic acid-based methods for on-site detection of plant pathogens : approaches and applications - Tomlinson, Jennifer A. (2012)
The ability to perform nucleic acid-based detection of plant pathogens away from conventional laboratory facilities has the potential to be beneficial in situations where results are required very rapidly or where resources and access to laboratory equipment are limited. Methods for use in such situations must combine sensitivity and specificity with rapid and simple workflows. The aim of this project was to investigate aspects of on-site testing for plant pathogens by developing detection methods for a range of target species. Detection methods based on loop-mediated isothermal amplification (LAMP) exhibit characteristics which make them potentially suitable for on-site testing. LAMP-based methods were developed for detection of plant pathogens with three potential non-laboratory testing scenarios in mind: testing during plant health inspection (assays for Phytophthora ramorum, P. kernoviae and Guignardia citricarpa); testing to assess inoculum levels in the processing of plant products (an assay for Botrytis cinerea); and testing in under-resourced settings (assays for Cassava brown streak virus and Ugandan cassava brown streak virus). In developing these detection methods, attempts were made to address some of the specific requirements of potential end-users of the tests in each case. For testing in the context of inspection, a particular emphasis was placed on the need for simple, rapid methods for nucleic acid extraction. As well as investigating the use of rapid extraction methods in conjunction with LAMP, work was also carried out to investigate how on-site nucleic acid extraction using lateral flow devices could be integrated with current field and laboratory testing for P. ramorum.